Description of a New Species of Pararrhynchium Saussure (Hymenoptera, Vespidae, Eumeninae) from Taiwan with a Catalogue of the Pararrhynchium Species - Kim, Kim; Kyu, Jeong; Yamane, Seiki (Zootaxa, 2007)
A new eumenine species, Pararrhynchium taiwanum sp. nov., from Taiwan is described. Based on the examination of holotype, the subspecies multifascitum Giordani Soika 1986 of Pararrhynchium paradoxum is actually a subspecies of P. ornatum (Smith), comb. nov. A catalogue of the nine species of Pararrhynchium Saussure is presented.